Lack of Association between ABO, PPAP2B, ADAMST7, PIK3CG, and EDNRA and Carotid Intima-Media Thickness, Carotid Plaques, and Cardiovascular Disease in Patients with Rheumatoid Arthritis - Raquel López-Mejías; Fernanda Genre; Mercedes García-Bermúdez; Begoña Ubilla; Santos Castañeda; Javier Llorca; Carlos González-Juanatey; Alfonso Corrales; José A. Miranda-Filloy; Trinitario Pina; Carmen Gómez-Vaquero; Luis Rodríguez-Rodríguez; et al. (Mediators of Inflammation)
Introduction. Rheumatoid arthritis (RA) is a polygenic disease associated with accelerated atherosclerosis and increased cardiovascular (CV) mortality. Recent studies have identified the ABO rs579459, PPAP2B rs17114036, and ADAMTS7 rs3825807 polymorphisms as genetic variants associated with coronary artery disease and the PIK3CG rs17398575 and EDNRA rs1878406 polymorphisms as the most significant signals related to the presence of carotid plaque in nonrheumatic Caucasian individuals. Accordingly, we evaluated the potential relationship between these 5 polymorphisms and subclinical atherosclerosis (assessed by carotid intima-media thickness (cIMT) and presence/absence of carotid plaques) and CV disease in RA. Material and Methods. 2140 Spanish RA patients were genotyped for the 5 polymorphisms by TaqMan assays. Subclinical atherosclerosis was evaluated in 620 of these patients by carotid ultrasonography technology. Results. No statistically significant differences were found when each polymorphism was assessed according to cIMT values and presence/absence of carotid plaques in RA, after adjusting the results for potential confounders. Moreover, no significant differences were obtained when RA patients were stratified according to the presence/absence of CV disease after adjusting for potential confounders. Conclusion. Our results do not confirm association between ABO rs579459, PPAP2B rs17114036, ADAMTS7 rs3825807, PIK3CG rs17398575, and EDNRA rs1878406 and subclinical atherosclerosis and CV disease in RA.